Phytoplankton Community as A Bioindicator for Water Quality of Sumi Dam, Bima Regency - Muhamad Hairil Anas; Lalu Japa; Khairuddin Khairuddin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The waters of the Sumi dam have an important role in accordance with the purpose of its construction. Therefore, monitoring of water quality becomes necessary because good water quality is an important requirement for every organism. This study aims to examine the water quality of the Sumi dam based on the community and species diversity of phytoplankton. The sampling location was determined based on the purposive sampling method. Water samples were taken in April 2021 using a 20 micron plankton net and preserved with formalin at a concentration of 4% preservation. The results showed that the identified phytoplankton community in the Sumi Dam consisted of 80 species and 13 classes. The index value of the diversity of phytoplankton species in the Sumi dam is high. Based on the index value of the diversity of phytoplankton species as a bioindicator, the waters of the Sumi dam are included in the unpolluted category.